The Effects of Habitat Disturbance on Adult Odonata Assemblages in Urban Freshwater Habitats of Southern Cape Coast Metropolis of Ghana - Badu, Isaac Kwame (University of Cape Coast, 2022)
Members of the insect Order Odonata have been widely used as indicators of the integrity of freshwater ecosystems. However, the effects of anthropogenically induced factors continue to affect their assemblages especially in urban areas. As such, this study was conducted to investigate the influence of human and natural habitat conditions on Odonate assemblages in freshwater habitats of southern Cape Coast Metropolis in the Central Region of Ghana. This was important to address the existing gap in knowledge on the Odonata species within the Metropolis and consequently, the effects of urban habitat conditions on Odonate assemblages in a tropical ecosystem. A total of four sampling visits per each of the 16 sites used for the study from January to June 2022, provided data on Odonata species. A habitat integrity index was generated for each site and used to categorise sites into 3 levels of disturbance: high, moderate, and least. Local climatic variables were measured and recorded for each study site. Twenty-six species of dragonflies and damselflies were recorded within the Metropolis. Generalised mixed effect model showed a varying significant effect of pH, water retention mechanism, condition of the riparian vegetation, preservation of the riparian vegetation and the presence or absence of cropland on dragonfly and damselfly abundance, diversity and compositions. A dragonfly biotic index was developed for habitat quality assessment within the Metropolis which showed that freshwater habitats within the Metropolis are experiencing some level of disturbance. There is therefore the need for conservation efforts to restore the integrity of the habitats surveyed and the entire Metropolis and the success of these actions can be monitored using the DBI.
xiv,129p:, ill.
Keywords: Odonata; Dragonfly; Damselfly; Freshwater; Urbanisation; Habitat Disturbance; Bioindicator